Novel loci for childhood body mass index and shared heritability with adult cardiometabolic traits. - Vogelezang, S.; Bradfield, J. P.; Ahluwalia, T. S.; Curtin, J. A.; Lakka, T. A.; Grarup, N.; Scholz, M.; van der Most, P. J.; Monnereau, C.; Stergiakouli, E.; Heiskala, A.; Horikoshi, M.; et al. (PLoS Genet, 2020)
The genetic background of childhood body mass index (BMI), and the extent to which the well-known associations of childhood BMI with adult diseases are explained by shared genetic factors, are largely unknown. We performed a genome-wide association study meta-analysis of BMI in 61,111 children aged between 2 and 10 years. Twenty-five independent loci reached genome-wide significance in the combined discovery and replication analyses. Two of these, located near NEDD4L and SLC45A3, have not previously been reported in relation to either childhood or adult BMI. Positive genetic correlations of childhood BMI with birth weight and adult BMI, waist-to-hip ratio, diastolic blood pressure and type 2 diabetes were detected (Rg ranging from 0.11 to 0.76, P-values <0.002). A negative genetic correlation of childhood BMI with age at menarche was observed. Our results suggest that the biological processes underlying childhood BMI largely, but not completely, overlap with those underlying adult BMI. The well-known observational associations of BMI in childhood with cardio-metabolic diseases in adulthood may reflect partial genetic overlap, but in light of previous evidence, it is also likely that they are explained through phenotypic continuity of BMI from childhood into adulthood.
Keywords: Adolescent; Adult; Blood Pressure; Body Mass Index; Cardiometabolic Risk Factors; Cardiovascular Diseases/*genetics/pathology; Child; Child, Preschool; Diabetes Mellitus, Type 2/*genetics/pathology; Female; *Genetic Predisposition to Disease; Genome-Wide Association Study/methods; Humans; Male; Menarche/genetics; Mendelian Randomization Analysis; Monosaccharide Transport Proteins/*genetics; Nedd4 Ubiquitin Protein Ligases/*genetics; Waist-Hip Ratio